Phylogenetic and transcriptomic characterization of insulin and growth factor receptor tyrosine kinases in crustaceans - Flores, Kaylie A.; Pérez-Moreno, Jorge L.; Durica, David S.; Mykles, Donald L. (Frontiers in Endocrinology, 2024)
Receptor tyrosine kinases (RTKs) mediate the actions of growth factors in metazoans. In decapod crustaceans, RTKs are implicated in various physiological processes, such molting and growth, limb regeneration, reproduction and sexual differentiation, and innate immunity. RTKs are organized into two main types: insulin receptors (InsRs) and growth factor receptors, which include epidermal growth factor receptor (EGFR), fibroblast growth factor receptor (FGFR), vascular endothelial growth factor receptor (VEGFR), and platelet-derived growth factor receptor (PDGFR). The identities of crustacean RTK genes are incomplete. A phylogenetic analysis of the CrusTome transcriptome database, which included all major crustacean taxa, showed that RTK sequences segregated into receptor clades representing InsR (72 sequences), EGFR (228 sequences), FGFR (129 sequences), and PDGFR/VEGFR (PVR; 235 sequences). These four receptor families were distinguished by the domain organization of the extracellular N-terminal region and motif sequences in the protein kinase catalytic domain in the C-terminus or the ligand-binding domain in the N-terminus. EGFR1 formed a single monophyletic group, while the other RTK sequences were divided into subclades, designated InsR1-3, FGFR1-3, and PVR1-2. In decapods, isoforms within the RTK subclades were common. InsRs were characterized by leucine-rich repeat, furin-like cysteine-rich, and fibronectin type 3 domains in the N-terminus. EGFRs had leucine-rich repeat, furin-like cysteine-rich, and growth factor IV domains. N-terminal regions of FGFR1 had one to three immunoglobulin-like domains, whereas FGFR2 had a cadherin tandem repeat domain. PVRs had between two and five immunoglobulin-like domains. A classification nomenclature of the four RTK classes, based on phylogenetic analysis and multiple sequence alignments, is proposed.